algebra
 👍 0
 👎 0
 👁 102

 👍 0
 👎 0
Respond to this Question
Similar Questions

math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

math
Consider the sequence of steps to solve the equation: 5(x  3) = 7x 2 Step 1 ⇒ 10(x  3) = 7x Step 2 ⇒ 10x  30 = 7x Step 3 ⇒ 3x  30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

Calculus
Use the fourstep process to find the slope of the tangent line to the graph of the given function at any point. f(x) = 16  10 x Step 2: f(x + h)  f(x) = Step 4: f'(x) = lim(h>0)(f(x + h) f(x))/h =

math
10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12? Use

MATH
Hannah is showing her work in simplifying (6.1 − 4.5) − 2.5 + 3.9. Identify any error in her work or reasoning. Step 1: (6.1 − 4.5) − 2.5 + 3.9 Step 2: 6.1 + (− 4.5 − 2.5) + 3.9 (associative property) Step 3: 6.1 − 7

math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

Help PLZ!!
consider the steps to simplify the expression. Which property is used to reach Step 3? Expression: 4 3 7 + 7 + (3 4 7 ) Step 1: = 4 3 7 + (3 4 7 ) + 7 Step 2: = 4 + ( 3 7 ) + (3) + ( 4 7 ) + 7 Step 3: = 4 + ( 3 7 ) + (

ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

Quick math help
In which step below does a mistake first appear in simplifying the expression? 0.5(12c+6)3(c+4)+10(c5) Step 1: 6c+33(c+4)+10(c5) Step 2: 6c+33c12+10(c5) Step 3: 6c+33c12+10c50 Step 4: 7c41 Please help me!!! Thank

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

Algebra
Debbie finished her algebra test early so she decided to check each of her answers. After checking her answer to question #10, she realized she made a mistake in her solution. In which step does Debbie make her mistake? Original

algebra 1
Can someone solve theses for me? Factor the polynomial x2 + 7x + 12 completely Factor the polynomial x2 – 4 completely Factor the polynomial 18a2b – 4ab + 10a completely x2 + 7x + 12 = (x+4)(x+3) x2 – 4 = (x+2)(x2) 18a2b
You can view more similar questions or ask a new question.